STRATEGI FINANCIAL LITERACY & FINANCIAL INCLUSION SEBAGAI TRIGGER KESEJAHTERAAN MASYARAKAT INDUSTRI KECIL KAWASAN WISATA GIRI KABUPATEN GRESIK JAWA TIMUR (JHP17 (Jurnal Hasil Penelitian), 2017)
Gresik regency has 27 tourist destinations supported by small and medium industries both in the sector of food and beverage, handicraft, Muslim fashion and its equipment, which has been established since several years ago. It seems that the development of this industry is stagnant although it is actually potential to be developed and can be a trigger for the welfare of the small industrial community of Gresik regency in East Java. The problems that occur in small and medium industry community of Giri regency of Gresik regency based on the survey result is that business actors still do not have financial literacy, marked by not understanding about financial planning, not yet separating recording and financial storage in their family or business. Besides, there is still limited socialization of financial inclusion so that in general they are still unbanked.              Based on factor analysis on financial literacy and financial inclusion, there are some attributes that significantly affect financial literacy of small and medium industries, namely financial planning, experience in finance, socialization of financial literacy from related parties, socio-economic status, economic attitude, financial behavior, financial attitude, financial crisis, government policy, financial education, demography, investment, saving, consumption, financial wellbeing, financial concerns, self control, old age, and gender. While the attributes of financial inclusion include credit management, knowledge of credit guidelines, consumer over in-debtedness, saving and deposit functions.               The strategies that should be done in the short term based on the attributes found in this study are: 1) to conduct financial literacy and financial inclusion education with attention to the significant attributes, 2) perform mentoring from financial planning to the preparation of financial statements, 3) giving motivation to separate between family finance and business finance 4) the government is expected to grow the role of cooperative as a saving and loan institution not only of loan alone so that the loan sharks will not play a role; 5) CSR programs need to be continuously implemented to pay attention to the social condition of the environment including small industry and medium, 6) is provided software for group accounting records. While the long-term strategy that is together with the tourism aspect is expected to become an industrial tourism that requires the production of small and medium industries based on economic potential, especially in the agricultural sector, processing industry, and tourism, and trade. Besides, it needs to be improved facilities and infrastructure that support tourism such as hotels and restaurants.